2020
DOI: 10.1098/rspb.2020.1118
|View full text |Cite|
|
Sign up to set email alerts
|

Weed diversity is driven by complex interplay between multi-scale dispersal and local filtering

Abstract: Arable weeds are key organisms for biodiversity maintenance and ecosystem service provision in agroecosystems. Disentangling the drivers of weed diversity is critical to counteract the global decline of farmland biodiversity. Even if distinct scale-dependent processes were alternatively proposed, no general framework unifying the multi-scale drivers of weed dynamics has yet emerged. Here, we investigate the joint effects of field- and landscape-scale processes on weed assemblages in 444 arable fields. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…We used sentinel preys to estimate natural pest control potential as it is a standard and efficient method related to predator activity (Lövei and Ferrante, 2017;Boetzl et al, 2020a) and pest regulation (Perez-Alvarez et al, 2019). In each cereal field, we measured natural pest control as the realized predation rate on two common pests: the aphid Acyrthosiphon pisum (Ximenez-Embun et al, 2014) which is commonly used to estimate aphid predation in cereal fields (Winqvist et al, 2011;Ricci et al, 2019), and the weed Viola arvensis (Petit et al, 2017) which is relatively common in cereal fields (Bourgeois et al, 2020). Weed seeds were bought at Herbiseed (Reading, United Kingdom).…”
Section: Experimental Designmentioning
confidence: 99%
“…We used sentinel preys to estimate natural pest control potential as it is a standard and efficient method related to predator activity (Lövei and Ferrante, 2017;Boetzl et al, 2020a) and pest regulation (Perez-Alvarez et al, 2019). In each cereal field, we measured natural pest control as the realized predation rate on two common pests: the aphid Acyrthosiphon pisum (Ximenez-Embun et al, 2014) which is commonly used to estimate aphid predation in cereal fields (Winqvist et al, 2011;Ricci et al, 2019), and the weed Viola arvensis (Petit et al, 2017) which is relatively common in cereal fields (Bourgeois et al, 2020). Weed seeds were bought at Herbiseed (Reading, United Kingdom).…”
Section: Experimental Designmentioning
confidence: 99%
“…First, the influence of regional frequency on local abundance suggests that dispersal dynamics across weed communities can maintain weed pressure and spillover. Weed dispersal plays a key role both in space (exchanges between fields, Bourgeois et al (2020)) and in time (through the seed bank, Mahaut, Fried, and Gaba (2018)) by reducing the probability of local extinction (rescue effect) and increasing local abundance (Hubbell, 1997). In addition, since specialization to arable habitat was positively related to local abundance, the dispersal dynamic of abundant species from regional to local level is assumed to occur predominantly for weeds that are specialist of arable habitat and, therefore, mainly between arable fields.…”
Section: Contribution Of Neutral Processes In Metacommunity Dynamicsmentioning
confidence: 99%
“…In very simple and homogeneous agricultural landscapes, natural habitat patches are extremely rare and are expected to contribute negligibly to crop biodiversity, while as landscape complexity increases, the diversity within crops is expected to increase by spillover from natural habitats until saturation at high levels of complexity (Concepción et al, 2008;Tscharntke et al, 2005). In the case of herbs, increases in natural habitat cover surrounding the crop could mitigate agricultural intensification effects at the farm scale, providing a pool of herb species less similar to the ones in the field core (Bourgeois et al, 2020). The interplay between the level of local agricultural intensification and the degree of landscape complexity is thought to determine the effectiveness of AES on farmland biodiversity recovery (Kleijn et al, 2011;Tscharntke et al, 2005Tscharntke et al, , 2012, and their synergistic effects have been confirmed in infield herb assemblages (Roschewitz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%